Hydrogeochemical Modeling of Groundwater in the Gadilam River Basin, South India - Prasanna, Mohan Viswanathan; Chidambaram, S. (Curtin University of Technology, Miri, Sarawak, 2009)
Hydrogeochemistry of a region is a reflection of hydrodynamic process, composition of lithology and physical constraints. The water chemistry is the resultant of all biogeochemical processes and reactions, which have acted on water from the moment it has condensed in atmosphere till the time it's discharged. A case study has been carried out in a varied lithological terrain with Archaean, Alluvium and Tertiary rocks to unravel the hydrogeochemical process. The dominant facies in the entire litho units is sodium - chloride type indicating saline nature in the groundwater. The speciation of bicarbonate, sulphate and phosphate in the groundwater samples in different litho units was determined using the computer program WATQ4F. This study reveals that higher speciation with increasing concentration of bicarbonate in summer and south west monsoon indicates static environment, whereas lesser speciation in north east monsoon and post monsoon indicates flushing environment in the basin. Higher speciation with lesser contribution of sulphate in summer and south west monsoon and an increasing trend of speciation in north east monsoon and post monsoon was observed.